الضغوط النفسية اثر جائحة كورونا وعلاقتها بالتوافق النفسي لدى تلاميذ البكالوريا - صالحي، إيناس, سوسة، نفيسة (جامعة الوادي university of Eloued, 2020)
ملخص الدراسة: تهدف الدراسة الحالية إلى الكشف عن مستوى الضغوط النفسية والتوافق النفسي اثر جائحة كورونا لدى التلاميذ البكالوريا ولهذا الغرض تم اختيار العينة بطريقة قصدية اعتمدنا على المنهج الوصفي وكذا مقياس الضغوط النفسية اثر جائحة كورونا ومقياس التوافق النفسي حيث تم تحويل مقاييس الدراسة إلى مقاييس الكترونية وتم نشرها عبر مواقع التواصل الاجتماعي (فايس بوك, انستقرام) حيث طلب من كل المشتركين إيصال المقياس لتلاميذ البكالوريا( ذكور,إناث) وبعد الحصول على العدد المناسب من عينة الدراسة 175 تلميذ وتلميذة قمنا بتحليل البيانات بواسطة الرزمة الإحصائية للعلوم الاجتماعية SPSS في تحليل بيانات أسفرت على نتائج التالية: - مستوى الضغوط النفسية اثر جائحة كورونا لدى تلاميذ البكالوريا مرتفع - مستوى التوافق النفسي عند تلاميذ البكالوريا منخفض - توجد علاقة ارتباطية عكسية بين الضغوط النفسية اثر جائحة كورونا والتوافق النفسي لدى تلاميذ البكالوريا - توجد فروق ذات دلالة إحصائية في الضغوط النفسية اثر جائحة كورونا تعزى لمتغير الجنس - توجد فروق ذات دلالة إحصائية في التوافق النفسي تعزى لمتغير الجنس كلمات مفتاحيه: الضغوط النفسية, جائحة كورونا, التوافق النفسي Abstract The current study aims to reveal the level of psychological stress and psychological adjustment after the corona pandemic among baccalaureate students For this purpose, the sample was chosen in an intentional way. We relied on the descriptive approach, as well as the psychological stress scale following the corona pandemic, and the psychological compatibility scale, where the study measures and were published on social media sites (facebook, instgram) where all participants were asked to deliver the scale to students of the baccalaureate (males, females) and after obtaining the appropriate number of the study sample of 175 male and female students, we also relied on the spss statistical package to analyze data that resulted in the following results: The level of psychological compatibility of baccalaureate students is low. There is an inverse correlation between psychological stress following the corona pandemic and psychological compatibility among baccalaureate students There are statistically significant differences in psychological stress due to the corona pandemic, due to the gender variable There are statistically significant differences in the psychological compatibility due to the gender variable Key words: psychological stress, corona pandemic, psychological compatibility.
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: التوافق النفسي، الضغوط النفسية، وباء كورونا; Compatibilité psychologique, stress psychologique et épidémie de Corona; Psychological compatibility, psychological stress, and the Corona epidemic